Genetic data of the ITS1-5.8S rDNA sequences of small liver flukes (Opisthorchiidae) from cats in Northern Vietnam - Hung, Nguyen Manh; Ho, Loan Thi; Tatonova, Yulia V. (Vietnam Journal of Biotechnology, 2020)
Domestic cats and humans are favorite final hosts for some hepatic trematodes of Opisthorchiidae. The present study examined the sequence variation in the nuclear ribosomal DNA (rDNA) region, including the internal transcribed spacer (ITS1) and the 5.8S gene, of two human opisthorchiid species Clonorchis sinensis (Cobbold, 1875) Looss, 1907 and Opisthorchis viverrini (Poirier, 1886) Stiles & Hassal, 1896, in cats sampled in Northern Vietnam. The length of 30 partial ITS1‒5.8S rDNA sequences of C. sinensis from different hosts and localities varied from 761 to 766 bp. The results showed completely identity for all investigated 5.8S rDNA sequences of C. sinensis. In contrast, the variations were revealed in the complete ITS1 sequences of C. sinensis. Three polymorphic sites, indel and new sites with intragenomic polymorphism were detected. The length of the complete ITS1 rDNA region ranged from 656 to 661 bp. There are no substitutions downstream of the 5 bp insertion, and the different ratio of nucleotide in polymorphic sites with presence/absence of insertion leads to the existence of 6 genotypes in the investigated samples. The major genotype was obtained in 70% of sequences, other genotypes were presented by 1, 2 or 3 sequences. Nucleotide diversity in whole sample of C. sinensis was 0.00122 ± 0.00073. Partial sequences of ITS1‒5.8S rDNA of O. viverrini were 745 bp in length, and no difference was observed. Phylogenetic analyses by neighbor joining phylogram inferred from ITS1‒5.8S rDNA of 3 sequences of O. viverrini and 30 sequences of C. sinensis were formed two separately monophyletic clades.